Differences In Parents' Perceptions Based On Economic Strata Towards The High School Separation Policy In Bandar Lampung - Arya Ndaya Dupa; Budhi Waskito; M. Denu Poyo (Universitas Dharmawangsa Medan, 2026)
The tradition of school farewell ceremonies in Indonesia has evolved into a significant academic and social milestone, yet it frequently sparks public controversy due to high implementation costs that burden lower-income families. In response, the Governor of Lampung issued Circular Letter No. 73 of 2025, which regulates these events to ensure they do not impose a financial burden. This study aims to analyze parents' perceptions of this policy and test whether significant differences in perception exist based on socioeconomic strata. Using a quantitative, data were collected through questionnaires from 207 parents in Bandar Lampung, representing diverse socioeconomic backgrounds. Data were analyzed using crosstabulation and the Pearson Chi-Square statistical test to examine the relationship between socioeconomic status and perception categories determined through a cut-off point method. The results reveal a highly significant difference in perception between parents from middle-high and middle-low socioeconomic strata (p=0.000). Parents from middle-low backgrounds exhibit overwhelming support (93% positive perception), viewing the policy as a crucial form of economic protection. Conversely, the middle-high group shows a notably higher level of resistance (38% negative perception), reflecting a conflict between policy objectives and the social expectations or prestige values of the upper class. These findings suggest that policymakers must design more inclusive and persuasive communication strategies to minimize sociological resistance and ensure equitable policy implementation.